Low-dose radiation therapy suppresses viral pneumonia by enhancing broad-spectrum anti-inflammatory responses via transforming growth factor-β production - Song, Ha-Yeon; Chen, Fengjia; Park, Hae Ran; Han, Jeong Moo; Ji, Hyun Jung; Byun, Eui-Baek; Kwon, Yeongkag; Kim, Min-Kyu; Ahn, Ki Bum; Seo, Ho Seong (Frontiers in Immunology, 2023)
Low-dose radiation therapy (LDRT) can suppress intractable inflammation, such as that in rheumatoid arthritis, and is used for treating more than 10,000 rheumatoid arthritis patients annually in Europe. Several recent clinical trials have reported that LDRT can effectively reduce the severity of coronavirus disease (COVID-19) and other cases of viral pneumonia. However, the therapeutic mechanism of LDRT remains unelucidated. Therefore, in the current study, we aimed to investigate the molecular mechanism underlying immunological alterations in influenza pneumonia after LDRT. Mice were irradiated to the whole lung 1 day post-infection. The changes in levels of inflammatory mediators (cytokines and chemokines) and immune cell populations in the bronchoalveolar lavage (BALF), lungs, and serum were examined. LDRT-treated mice displayed markedly increased survival rates and reduced lung edema and airway and vascular inflammation in the lung; however, the viral titers in the lungs were unaffected. Levels of primary inflammatory cytokines were reduced after LDRT, and transforming growth factor-β (TGF-β) levels increased significantly on day 1 following LDRT. Levels of chemokines increased from day 3 following LDRT. Additionally, M2 macrophage polarization or recruitment was increased following LDRT. We found that LDRT-induced TGF-β reduced the levels of cytokines and polarized M2 cells and blocked immune cell infiltration, including neutrophils, in BALF. LDRT-induced early TGF-β production was shown to be a key regulator involved in broad-spectrum anti-inflammatory activity in virus-infected lungs. Therefore, LDRT or TGF-β may be an alternative therapy for viral pneumonia.